Effects of Physical Exercise on Executive Function in Schizophrenia: Systematic Review and Meta-Analysis - Nuria Pérez-Romero; Christian Campos-Jara; Caterina Pesce; Sergio Araya Sierralta; Enrique Cerda-Vega; Rodrigo Ramirez-Campillo; Rodrigo Campos-Jara; Cristian Martínez-Salazar; Cristián Arellano-Roco; Victoria Hernández-Cifuentes; Falonn Contreras-Osorio (Sports)
Executive functions are often impaired in individuals with schizophrenia spectrum disorders. Understanding the impact of physical exercise on these cognitive domains is essential for developing effective interventions. The aim of this review is to assess the effect of physical exercise on executive functions in adults diagnosed with schizophrenia spectrum disorders. A systematic search was conducted in Web of Science, PubMed, Scopus, and EBSCO, initially from inception through January 2024, followed by an update through January 2025. Studies involved adults diagnosed with schizophrenia spectrum disorders, employed physical exercise as an intervention, and measured executive functions as outcomes. The selection followed PRISMA guidelines, with inclusion determined by consensus among multiple reviewers. Data extraction and risk of bias assessment were conducted independently by two reviewers using the Cochrane RoB 2 tool and GRADE approach for certainty of evidence. Meta-analyses were performed using random-effects models, with effect sizes (ES) and 95% confidence intervals (CI) calculated for each outcome. From 1517 records, 9 studies were included in the meta-analysis. The analysis revealed a small but significant effect of physical exercise on working memory (ES = 0.300, 95% CI = 0.060–0.539, p = 0.014; I2 = 0.0%, Q = 2.2, p = 0.951) and a non-significant effect on emotion recognition (ES = 0.51, 95% CI = −0.291–1.303, p = 0.213; I2 = 83%), inhibition (ES = 0.156, 95% CI = −0.173 to 0.484, p = 0.353; I2 = 0.0%, Q = 1.1, p = 0.781), and cognitive flexibility (ES = 0.240, 95% CI = −0.270 to 0.749, 95% PI = −1.706 to 2.185; p = 0.356; I2 = 53.2%, Q = 3.0, p = 0.094). Physical exercise, particularly aerobic exercise, appears to have a small beneficial effect on working memory in individuals with schizophrenia spectrum disorders. However, the evidence for its effect on emotion recognition is less clear and may be influenced by the type of exercise, such as yoga. Further research is needed to provide more robust conclusions. PROSPERO registration number: CRD42023392295.